The outcome and the risk factors of mucormycosis among patients with hematological diseases: a systematic and meta-analysis - Shen, Meixiao; Wang, Juan; Lei, Meiqing; Wang, Zhiming (Frontiers in Medicine, 2023)
Objectives Mucorale has come into a significant pathogen over recent decades. Nonetheless, mucormycosis-related mortality rates among patients with hematological disorders remain unascertained. Thus, we conducted a meta-analysis to determine mortality rates of mucormycosis in patients with hematology-related conditions. Methods We scoured PubMed, Embase, and Web of Science for original papers exploring the intersection of Mucormycosis and Hematological Diseases (from 2000 to 2022). We scrutinized the overall mortality across three distinct periods, as well as differentiating between high-income and middle-income nations. We further evaluated the pooled mortality and the risk differential (RD) across several subgroups. Results The overall mortality rate for hematology patients with mucormycosis was 61%, within a 95% confidence interval (CI) of 0.54–0.68. A significant observation was that mortality rates were somewhat lower in high-income countries compared to middle-income countries (0.60 versus 0.64, p = 0.45). Importantly, we discovered that a combination of surgical and medical treatment significantly improved survival rates compared to medical treatment alone [mortality 0.49 versus 0.67, RD -0.19 (95%CI -0.38-0.00, I2 63.7%)]. As might be expected, disseminated mucormycosis posed a significantly higher risk of death compared to isolated mucormycosis [0.60 versus 0.57, RD death 0.16 (95%CI 0.03–0.28)]. Additionally, our analysis showed no discernible differences in survival rates between genders, between patients with and without breakthrough infection, between those who received mucor-active or mucor-inactive drugs prior to mucor infection, or between those on a multi-drug regimen and those on a single drug treatment. Conclusion Despite the high mortality rates associated with mucormycosis in patients with hematological disorders, those receiving both medical and surgical interventions, as well as those with isolated infection sites, exhibited improved survival outcomes. Conversely, factors such as gender, the presence of breakthrough infection, the use of mucor-active drugs before mucor infection, and multi-drug administration did not significantly influence patient outcomes.